Sex Differences in Brain Aromatase Activity: Genomic and Non-Genomic Controls - Balthazart, Jacques; Charlier, Thierry D.; Cornil, Charlotte A.; Dickens, Molly J.; Harada, Nobuhiro; Konkle, Anne T.; Voigt, Cornellia; Ball, Gregory F. (Frontiers in Endocrinology, 2011)
Aromatization of testosterone into estradiol in the preoptic area plays a critical role in the activation of male copulation in quail and in many other vertebrate species. Aromatase expression in quail and in other birds is higher than in rodents and other mammals, which has facilitated the study of the controls and functions of this enzyme. Over relatively long time periods (days to months), brain aromatase activity and transcription are markedly (4-6 fold) increased by genomic actions of sex steroids. Initial work indicated that the preoptic aromatase activity is higher in males than in females and it was hypothesized that this differential production of estrogen could be a critical factor responsible for the lack of behavioral activation in females. Subsequent studies revealed, however, that this enzymatic sex difference might contribute but is not sufficient to explain the sex difference in behavior. Studies of aromatase activity, immunoreactivity and mRNA concentrations revealed that sex differences observed when measuring enzymatic activity are not necessarily observed when one measures mRNA concentrations. Discrepancies potentially reflect post-translational controls of the enzymatic activity. Aromatase activity in quail brain homogenates is rapidly inhibited by phosphorylation processes. Similar rapid inhibitions occur in hypothalamic explants maintained in vitro and exposed to agents affecting intracellular calcium concentrations or to glutamate agonists. Rapid changes in aromatase activity have also been observed in vivo following sexual interactions or exposure to short-term restraint stress and these rapid changes in estrogen production modulate expression of male sexual behaviors. These data suggest that brain estrogens display most if not all characteristics of neuromodulators if not neurotransmitters. Many questions remain however concerning the mechanisms controlling these rapid changes in estrogen production and their behavioral significance.